Ethical Principles Of Providing Ideological Safety - Saida Karimova (Periodica Journal, 2022)
In the article, under the conditions of today's globalization, geopolitical struggles of different ideologies are going on in the ideological field of the world. Uzbekistan cannot stay away from it, due to the increasing ideological threats; we need to pay special attention to the issue of ideological security and in this process, and the role of the family, in terms of raising children will go.
Keywords: education; Family; educationideological security; moral